1983
DOI: 10.1016/0014-5793(83)81123-5
|View full text |Cite
|
Sign up to set email alerts
|

NMR analyses on the molecular mechanism of the conformational rigidity of 2‐thioribothymidine, a modified nucleoside in extreme thermophile tRNAs

Abstract: 'H-NMR analyses have been made on the conformations of Zthioribothymidine (s2T), 2-thiodeoxyribothyrnidine (s2dT), as well as ribothymidine (T) and deoxyribothymidine (dT). s2T and s2dT exclusively take the anti form rather than the syn form. The C3 ' -endo-gg form of the sugar moiety is remarkably stabilized on modification of T to s2T, but not on m~ifi~tion of dT to s2dT. The steric effects of the 2-~ioc~bonyl group and the 2'-hydroxyl group cause the rigidity of the C3'-endo-gg form of s2T. Such rigidity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 12 publications
0
33
0
Order By: Relevance
“…A number of these modifications serve to stabi-lize the C-3Ј-endo form of ribose in the polynucleotide chain, effectively stabilizing the A-type helical conformation that is common to RNA (26,27,57). They also promote stability through hydrogen bonding and enhanced base stacking (13), and they provide nuclease protection by ribose methylation (1).…”
Section: Discussionmentioning
confidence: 99%
“…A number of these modifications serve to stabi-lize the C-3Ј-endo form of ribose in the polynucleotide chain, effectively stabilizing the A-type helical conformation that is common to RNA (26,27,57). They also promote stability through hydrogen bonding and enhanced base stacking (13), and they provide nuclease protection by ribose methylation (1).…”
Section: Discussionmentioning
confidence: 99%
“…We have already found that the C3'-endo form is predominant in 2-thiopyrimidine nucleosides and nucleotides (16,18). The remarkable stability of the C3'-endo form is due to the steric interaction between the bulky 2-thiocarbonyl group and the 2'-hydroxyl group (17). As shown in Table 1, the relative stabilities of the C3'-endo form of 2-thiouridine derivatives (s2U, ps2U, and m5s2U) are higher, by 0.8 kcal/mol, than those of non-thiosubstituted derivatives (uridine, pU, and m5U).…”
mentioning
confidence: 99%
“…It was reported that s 2 U derivatives prefer C3 0 -endo ribose puckering. [28][29][30] This conformational predominance is known to be caused by steric repulsion between the 2-thiocarbonyl group of s 2 U and the 2 0 -hydroxy group. 28 The C3 0 -endo predominance observed could be explained by the same type of steric repulsion.…”
Section: -15mentioning
confidence: 99%